2010
DOI: 10.1093/carcin/bgq125
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-dependent and -independent transport of arsenic by the human multidrug resistance protein 2 (MRP2/ABCC2): implications for the mutual detoxification of arsenic and selenium

Abstract: Simultaneous exposure of lab animals to toxic doses of the human carcinogen arsenic (As) and the essential trace element selenium (Se) results in a remarkable mutual detoxification. A likely basis for this is the in vivo formation and biliary excretion of seleno-bis(S-glutathionyl) arsinium ion [(GS)(2)AsSe](-); however, the transport protein responsible for the biliary efflux of [(GS)(2)AsSe](-) has not been identified. The multidrug resistance protein 2 (MRP2/ABCC2) is an adenosine triphosphate (ATP)-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 43 publications
0
40
1
2
Order By: Relevance
“…To survive various toxic environments, vertebrates including fish have developed defensive mechanisms against toxicants and MRP transporters appears to be the main factors involved in the multi-xenobiotic resistance developed during the evolution of aquatic organisms (Sauerborn Klobucar et al, 2010). Mammalian ABCC2s have been shown to be critical in the detoxification and elimination of heavy metals, including mercury (Aleo et al, 2005;Zalups and Bridges, 2010), arsenite (Carew and Leslie, 2010;Kala et al, 2000) and platinum (Guminski et al, 2006;Surowiak Livers and intestines were taken from 4 females, and kidneys were taken from 4 females and 4 males. Same tissues from different fish were mixed for isolation of total RNA and subjected to qRT-PCR analysis of abcc2 mRNA levels relative to the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To survive various toxic environments, vertebrates including fish have developed defensive mechanisms against toxicants and MRP transporters appears to be the main factors involved in the multi-xenobiotic resistance developed during the evolution of aquatic organisms (Sauerborn Klobucar et al, 2010). Mammalian ABCC2s have been shown to be critical in the detoxification and elimination of heavy metals, including mercury (Aleo et al, 2005;Zalups and Bridges, 2010), arsenite (Carew and Leslie, 2010;Kala et al, 2000) and platinum (Guminski et al, 2006;Surowiak Livers and intestines were taken from 4 females, and kidneys were taken from 4 females and 4 males. Same tissues from different fish were mixed for isolation of total RNA and subjected to qRT-PCR analysis of abcc2 mRNA levels relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that heavy metals can be detoxified and eliminated from cells by some of MRP transporters after conjugation to glutathione (Aleo et al, 2005;Chen et al, 1997;Ishikawa et al, 1994;Preveral et al, 2009). ABCC2/MRP2 has been shown to play important roles in the detoxification of heavy metals, including mercury (Aleo et al, 2005;Zalups and Bridges, 2010), arsenite (Carew and Leslie, 2010;Kala et al, 2000) and platinum (Guminski et al, 2006;Surowiak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For stable expression of MRP3, MRP4, MRP5, and empty pcDNA3.1(1), 2.5 Â 10 5 HEK293 cells were seeded in each well of a six-well plate, and 24 hours later DNA (1 mg) was transfected using either 3 ml FuGENE 6 transfection reagent (Roche Diagnostics Co., Mannheim, Germany), according to the manufacturer's instructions, or the calcium phosphate transfection method as described previously (Carew and Leslie, 2010). Forty-eight hours later, cells were subcultured (1:24) onto six-well plates and medium was replaced with Dulbecco's modified Eagle's medium containing 1000 mg/ml G418 (Invitrogen) and 10% fetal bovine serum.…”
Section: /Kmentioning
confidence: 99%
“…In vivo studies of Mrp2 (Abcc2)-deficient (TR 2 ) Wistar rats show that Mrp2 is responsible for the biliary excretion of As(GS) 3 and MMA(GS) 2 (Kala et al, 2000). As(GS) 3 and the seleno-bis (S-glutathionyl) arsinium ion [(GS) 2 AsSe] 2 are substrates for human MRP2 in vitro (Carew and Leslie, 2010). Despite the important roles MRP1 and MRP2 play in protecting cells and tissues from arsenic, neither protein is localized to the basolateral surface of human hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that arsenic in combination with glutathione can be excreted by MRPs and PGPs (Li et al, 2007;Drobna et al, 2010;Carew and Leslie, 2010). Li et al (2007) have shown that when cells subjected to long-term exposure to a low-dose arsenic environment are subjected to acute arsenic exposure their sensitivity to arsenic reduces significantly.…”
Section: Arg1 Gene and The Arsenic Resistance Of Cellsmentioning
confidence: 99%